Biology and conservation of the river dolphins proceedings of the Workshop on Biology and Conservation of the Platanistoid Dolphins held at Wuhan, People's Republic of China, October 28-30, 1986 - Perrin, W. F.; Brownell, Robert L.; Kaiya, Zhou; Jiankang, Liu (IUCN, 1989)
Occasional papers of the IUCN Species Survival Commission; no.3